Effects of exercise in non-treatment seeking adults with alcohol use disorder: A three-armed randomized controlled trial (FitForChange). (1st March 2022) - Gunillasdotter, Victoria; Andréasson, Sven; Jirwe, Maria; Ekblom, Örjan; Hallgren, Mats
Abstract: Background: Most individuals with alcohol use disorder (AUD) do not seek treatment. Stigma and the desire to self-manage the problem are likely explanations. Exercise is an emerging treatment option but studies in non-treatment seeking individuals are lacking. We compared the effects of aerobic exercise, yoga, and treatment as usual (phone-based support) on alcohol consumption in non-treatment seeking adults with AUD. Methods: Three-group parallel, single blind, randomized controlled trial. 140 physically inactive adults aged 18–75 diagnosed with AUD were included in this community-based trial. Participants were randomized to either aerobic exercise (n = 49), yoga (n = 46) or treatment as usual (n = 45) for 12-weeks. The primary study outcome was weekly alcohol consumption at week 13 (Timeline Follow-back). Results: A significant decrease in weekly alcohol consumption was seen in all three groups: aerobic exercise (mean ∆ = − 5.0, 95% C = − 10.3, − 3.5), yoga group (mean ∆ = − 6.9, 95% CI = − 10.3, − 3.5) and TAU (mean ∆ = − 6.6, 95% CI = − 8.8, − 4.4). The between group changes were not statistically significant at follow-up. Per-protocol analyzes showed that the mean number of drinks per week reduced more in both TAU (mean ∆ = − 7.1, 95% CI = − 10.6, − 3.7) and yoga (mean ∆ = − 8.7, 95% CI = − 13.2, − 4.1) compared to aerobic exercise (mean ∆ = − 1.7, 95% CI = − 4.4, 1. 0), [F(2, 55) = 4.9, p = 0.011]. Conclusions: Participation in a 12-week stand-alone exercise program was associated with clinically meaningful reductions in alcohol consumption comparable to usual care (phone counseling) by an alcohol treatment specialist. Highlights: We evaluated the effects of aerobic exercise and yoga as stand-alone treatment for adults with alcohol use disorder. Many adults with alcohol use disorder are interested in exercise to help reduce their alcohol consumption. Exercise alone, in particular yoga-based exercise, had effects on consumption comparable to phone counselling by a clinician.